FRI0158 Clinical Evaluation Usefulness of Standardized Protocol Strategies of Dose Reduction in Patients with Rheumatoid Arthritis in Clinical Remission Treated with Biologic Therapies. The Optibio Study. (15th July 2016) - Bejerano, C.; Oreiro, N.; Fernandez-Lopez, C.; Pinto-Tasende, J.A.; Atanes, A.; Aspe, B.; Graña, G.; Freire, M.; Acasuso, M.; De Toro, J.; Blanco, F.J.
Abstract : Objectives: The OPTIBIO study is a clinical trial whose primary endpoint is to evaluate the proportion of patients that after one year are maintained in clinical remission with a dose reduction treatment regimen of biological therapy in patients with Rheumatoid Arthritis, and to evaluate if the proportion of patients in remission with new regimen dose of treatment is not inferior to patients in remission with standard dose regimen. In our present work, we describe the preliminary results obtained so far. Methods: Open, randomized and controlled study of patients in clinical remission (DAS 28 <2.6 or SDAI <5 or ACR/EULAR 2011 criteria) at least 6 months followed in Third level Hospital Rheumatology Department. Patients treated with TNF inhibitors therapies (Etanercept, Infliximab, Adalimumab, Certolizumab, Golimumab), Tocilizumab and Abatacept. Patients are assigned to two groups randomly. Intervention group: according to a standardized protocol of dose reduction of biological therapies. Control group: according to standard dose regimen. Flare is considered when DAS28>2.6 or SDAI>5 or ACR/EULAR criteria are not fulfilled. Patients are following during after a minimum period of one year and maximum period of 3 years. The frequency of visits is every 12 weeks. Results: 58 patients have been included from 14 April 2014 to 11 January 2016. Forty-eight women (82, 76%) and 10 men (17, 24%) with an average age of 59, 34 ± 11, 28 years. Twenty-nine in standard regimen dose and 29 patients in dose reduction regimen. None of the patients had tender or swollen joints at the beginning. At baseline, ESR and CRP values were 16, 84 mm/1hour y 0, 22 mg/dl respectively. DAS 28-ESR value was 1, 84 ± 0.72 and DAS28-CRP was 1.34 ± 0.26. Rheumatoid Factor is positive in 79.31%. Forty-one patients have erosive disease. Seventeen patients have presented a flare: 24, 13% in control group and 34, 48% in intervention group without statistical signification (p=0.5640). The characteristics of the patients are described in table 1 . Statistic differences were not found. Conclusions: Preliminary results show that dose reduction of biological therapies with a standardized protocol it does not seem to increase reactivation risk of disease activity. Disclosure of Interest: None declared